Implementing a low‐starch biscuit‐free diet in zoo gorillas: The impact on behavior. Issue 1 (4th January 2014) - Less, E.H.; Bergl, R.; Ball, R.; Dennis, P.M.; Kuhar, C.W.; Lavin, S.R.; Raghanti, M.A.; Wensvoort, J.; Willis, M.A.; Lukas, K.E.
<x xml:space="preserve">Abstract</x> In the wild, western lowland gorillas travel long distances while foraging and consume a diet high in fiber and low in caloric density. In contrast, gorillas in zoos typically consume a diet that is low in fiber and calorically dense. Some items commonly used in captive gorilla diets contain high levels of starch and sugars, which are present at low levels in the natural diet of gorillas. Diet items high in simple carbohydrates are associated with obesity and heart disease in humans. Typical captive gorilla diets may also encourage undesirable behaviors. In response to these issues, we tested the behavioral impact of a diet that was biscuit‐free, had low caloric density, and which was higher in volume at five institutions. We hypothesized that this diet change would reduce abnormal behaviors such as regurgitation and reingestion (R/R), decrease time spent inactive, and increase time spent feeding. The biscuit‐free diet significantly reduced (and in the case of one zoo eliminated) R/R and may have reduced hair‐plucking behavior. However, an increase in coprophagy was observed in many individuals following the diet change. The experimental diet caused a general increase in time the gorillas spent feeding, but this increase did not occur across all institutions and varied by individual. Interestingly, the overall time gorillas spent inactive actually increased with this diet change. Future research will examine these behavioral changes in a greater number of individuals to determine if the results remain consistent with these preliminary findings. Additionally, future research will examine the physiological impact of this diet change. Zoo Biol. 33:63–73, 2014. © 2014 Wiley Periodicals Inc.